2001
DOI: 10.1021/es002059b
|View full text |Cite
|
Sign up to set email alerts
|

MTBE Ambient Water Quality Criteria Development:  A Public/Private Partnership

Abstract: A public/private partnership was established in 1997, under the administrative oversight of the American Petroleum Institute (API), to develop aquatic toxicity data sufficient to calculate ambient water quality criteria for methyl tertiary-butyl ether (MTBE), a gasoline oxygenate. The MTBE Water Quality Criteria Work Group consisted of representatives from private companies, trade associations, and USEPA. Funding was provided by the private entities, while aquatic biological/toxicological expertise was provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 13 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…In spite of the bans in some countries, it is still the second most common volatile organic compound in shallow groundwater (Levchuk et al, 2014). Due to its genotoxicity, its hazard of causing skin and eye irritation and its unpleasant odour (Mancini et al, 2002), the existence of MTBE in aquatic environments has raised considerable public concerns.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the bans in some countries, it is still the second most common volatile organic compound in shallow groundwater (Levchuk et al, 2014). Due to its genotoxicity, its hazard of causing skin and eye irritation and its unpleasant odour (Mancini et al, 2002), the existence of MTBE in aquatic environments has raised considerable public concerns.…”
Section: Introductionmentioning
confidence: 99%
“…1634-04-4), in a typical gasoline formulation, has an equilibrium water concentration of approximately 5000 mg/L at room temperature and readily partitions into aquatic systems (4). The toxicity of MTBE is low as compared to environmental exposures in both mammals and aquatic organisms (5)(6)(7)(8). Thus, it has been suggested that the risk of adverse effects because of MTBE in aquatic systems is minimal (8).…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of MTBE is low as compared to environmental exposures in both mammals and aquatic organisms (5)(6)(7)(8). Thus, it has been suggested that the risk of adverse effects because of MTBE in aquatic systems is minimal (8).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is common for EPA WQC documents to present only deterministic values for criteria (e.g., USEPA 2009). Several peer-reviewed publications that present proposed WQC using the 1985 Guidelines also provide only deterministic values with no quantitative characterization of uncertainty (Hohreiter and Rigg 2001, Tong et al 1996, Yin et al 2003, Mancini et al 2002, Augspurger et al 2003, March et al 2007). …”
Section: Comparison To Other Hc5 Uncertainty Estimates From the Litermentioning
confidence: 99%